Scientific Evolution of the Concept of Integrated Transport System in Meta-Analysis - Nico Djundharto Djajasinga; Sri Sarjana; Sudirman Anggada (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This study aims to analyze the scientific evolution of the integrated transport system concept in a meta-analysis. This study applies a qualitative approach that utilizes scientific development to various scientific journal publications on the idea of an integrated transportation system. Scientific journal data analysis was developed through scientific evolution with a meta-analysis approach to obtain knowledge mapping. Bibliometric analysis is implemented in a meta-analysis approach followed by applying relevant procedures in analyzing the concept of an integrated transportation system for the development of knowledge and technology. The analytical technique in this research is a bibliometric analysis by developing the VOSviewer program based on the concept of an integrated transportation system under study. The initial step is to collect databases from various sources of scientific journals so that multiple journals that are relevant to the proposed theme are obtained. Based on the results of the analysis by developing the VOSviewer program based on the concept of an integrated transportation system, articles related to the integrated transportation system from 1948 to 2021, it can be concluded that several keywords become the core of this field of study, including Policy Implementation, Social Welfare, Sustainable Transport, Public Participation, Planning, Development.